Hukum Profetik dalam Praktik Ketatanegaraan dan Penegakan Hukum - Ady Supryadi; Tin Yuliani; Anies Prima Dewi; Nasri Nasri; Sarudi Sarudi; Titin Titawati (Yayasan Pendidikan Kardin Assidiq, 2025)
Introduction: Prophetic law is a legal framework grounded in prophetic values, specifically humanisation (amar ma'ruf), liberation (nahi munkar), and transcendence (tu'minuna billah). Its main aim is to achieve substantive justice and enhance the welfare of the people. Objective: This article seeks to examine and analyse the implementation of prophetic law within state administration and law enforcement practices in Indonesia. Method: The research employs a normative legal research method, using philosophical, conceptual, and regulatory approaches. Results: The findings indicate that, normatively, the values of prophetic law are reflected in the constitutional principles outlined in the 1945 Constitution of the Republic of Indonesia. These principles particularly emphasise the guarantee of human rights, the pursuit of social justice, and the protection of the populace. However, in practice, implementing these values faces several challenges. These include the predominance of a legal positivist approach, the weak moral compass of law enforcement officials, and the insufficient integration of transcendental values in the formulation and implementation of laws. Conclusions and Recommendations: The conclusions emphasise the necessity of enhancing the practice of law by reformulating national legal policies to better align with prophetic values.